From Mitochondria to Atherosclerosis: The Inflammation Path - Juan M. Suárez-Rivero; Carmen J. Pastor-Maldonado; Suleva Povea-Cabello; Mónica Álvarez-Córdoba; Irene Villalón-García; Marta Talaverón-Rey; Alejandra Suárez-Carrillo; Manuel Munuera-Cabeza; José A. Sánchez-Alcázar (Biomedicines, 2021)
Inflammation is a key process in metazoan organisms due to its relevance for innate defense against infections and tissue damage. However, inflammation is also implicated in pathological processes such as atherosclerosis. Atherosclerosis is a chronic inflammatory disease of the arterial wall where unstable atherosclerotic plaque rupture causing platelet aggregation and thrombosis may compromise the arterial lumen, leading to acute or chronic ischemic syndromes. In this review, we will focus on the role of mitochondria in atherosclerosis while keeping inflammation as a link. Mitochondria are the main source of cellular energy. Under stress, mitochondria are also capable of controlling inflammation through the production of reactive oxygen species (ROS) and the release of mitochondrial components, such as mitochondrial DNA (mtDNA), into the cytoplasm or into the extracellular matrix, where they act as danger signals when recognized by innate immune receptors. Primary or secondary mitochondrial dysfunctions are associated with the initiation and progression of atherosclerosis by elevating the production of ROS, altering mitochondrial dynamics and energy supply, as well as promoting inflammation. Knowing and understanding the pathways behind mitochondrial-based inflammation in atheroma progression is essential to discovering alternative or complementary treatments.